RANCANG BANGUN ROBOT PEMBERSIH RUANGAN BERBASIS ARDUINO UNO DENGAN KENDALI APLIKASI ANDROID - Alfith, Alfith; Effendi, Asnal; Dasman, Dasman; Pratama, Frengki Ananda (Ensiklopedia of Journal, 2022)
The development of science and technology is currently very rapid, especially in the field of technology that affects people's lives to move forward, one of which is using robotics, in principle, the purpose of creating robots is to facilitate human work, especially since the progress of the times demands effective and efficient human work. For example, in cleaning the house, a robot was made that can help someone clean his house. This robot will later clean the floor of the house from dirt in the form of dust. This cleaning robot will be controlled with an Android application. That has been made previously and will be combined with a wireless robot control using the HC-05 Bluetooth module, which will transmit control from android to Arduino Uno as the brain of this room cleaning robot, and will process data. From android applications such as forward and backward, and turn commands and also the command  to turn on and turn off the vacuum cleaner which can also be controlled from this Android application. For the movement of the robot itself, it will use a PG28 DC Motor which will be controlled by the BTS7960 Driver. From the results of tests